KAJIAN SEDIMENT DELIVERY RATIO DI DAERAH TANGKAPAN WADUK KEDUNG OMBO - , Dadang Ismu Hardiyan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kedung Ombo reservoir is one of the reservoirs that have a huge potential in providing raw water requirements and irrigation water in the province of Central Java. Kedung Ombo reservoir is located in the upstream of Serang river which catchment area is 598.04 km2. The catchment area of Kedung Ombo reservoir contains a large amount of soil erosion. The rate of soil erosion impacts on the rate of sedimentation in the catchment area of Kedung Ombo reservoir which results to reduction in the capacity of the reservoir. The rate of soil erosion in the catchment area of Kedung Ombo reservoir analyzed using Geografic Information System (GIS) application with the method of the Universal Soil Loss Equation (USLE). Actual Sediment Delivery Ratio (SDR) is calculated using the actual measurement results of echosounding and estimated SDR is calculated using the equation from the literature. The results of the calculation show that the rate of soil erosion in the catchment area of Kedung Ombo Reservoir is 154.08 tons/ha/year or 9.53 mm/year. The actual value of SDR is 0.293, while the estimated value of SDR is 0.229. Actual sediment yield in the period of 9 years is 15.01 million m3, while the estimated sediment yield is 12.86 million m3. The largest sediment yield is derived from Gading Sub-basin of 0.60 million m3/year. Gading Sub-basin has been a top priority in controling soil erosion and sedimentation in the catchment area of Kedung Ombo Resevoir.